High Reflectivity and Low Reflectivity Properties on OCTA Influence the Detection of Macular Neovascularization in AMD - Arrigo, Alessandro; Aragona, Emanuela; Bordato, Alessandro; Amato, Alessia; Saladino, Andrea; Bandello, Francesco; Parodi, Maurizio Battaglia (Frontiers in Physics, 2021)
Background: In this study, we aimed to discriminate high reflectivity and low reflectivity macular neovascularization (MNV) lesions secondary to age-related macular degeneration (AMD)and to assess the influence of blood flow features on the amount of MNV detected by optical coherence tomography angiography (OCTA). Methods: The study was designed as observational, cross-sectional. Type 1 and type 2 MNV lesions were included. All the patients underwent fluorescein angiography (FA), indocyanine green angiography (ICGA) and OCTA. MNV size was calculated on early FA for type 2 MNV and on both early and late phases of ICGA for type 1 lesions. From OCTA, we calculated both MNV size and MNV reflectivity. We assessed the agreement between FA/ICGA and OCTA MNV sizes. Moreover, we studied the relationship between MNV reflectivity properties and MNV OCTA detection. Results: Fifty eyes (50 patients) were included. MNV was identified as follows: 35 /70%) type 1 and 15 (30%) type 2. We found a good agreement between early ICGA size and OCTA size for type 1 MNV (2.10±1.91mm2 vs 2.09±1.87mm2; p>0.05), whereas MNV lesions turned out to be remarkably bigger on late ICGA phase (3.41±2.87mm2; p<0.01). Interestingly, OCTA well-matched with FA in terms of MNV size for type 2 lesions (2.36±2.15mm2 vs 2.37±2.25mm2). MNV reflectivity was higher in type 2 MNV and it was strongly associated with the OCTA ability to reconstruct the neovascular network. Conclusions: Our study quantitatively showed that MNV filling pattern and MNV blood flow reflectivity features influence the OCTA detection of the MNV in its entirety.